2011
DOI: 10.1111/j.1399-3046.2011.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable disease progression after successful stem cell transplantation: Prospective follow‐up investigations in eight patients with Hurler syndrome

Abstract: We report the results of a prospective, standardized follow-up programme of eight children (median age at SCT 1.2 yr) with mucopolysaccharidosis (MPS1H, M. Hurler) transplanted using a fludarabine-based SCT. SCT resulted in stable engraftment without transplant-related mortality. All patients are alive, engrafted and in ambulatory care. During follow-up (median five yr, 1.9-8 yr), six of eight showed developmental delay (two severe, two mild/no), all eight had spinal deformities and one received hip surgery fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, several studies have reported that subsequent cognitive deterioration occurs after stem cell transplantation, justifying the use of intrathecal enzyme replacement therapy to prevent further decline. 32,33 Our results suggest that the decline in IQ observed in some cases may be due to sequelae of early brain injury due to accumulation of glycosaminoglycans. Patients who were younger than 9 months at the time of transplantation had minimal injury and were still cognitively normal; thus, transplantation of stem cells to supply the missing enzyme prevented further injury.…”
Section: Discussionmentioning
confidence: 70%
“…However, several studies have reported that subsequent cognitive deterioration occurs after stem cell transplantation, justifying the use of intrathecal enzyme replacement therapy to prevent further decline. 32,33 Our results suggest that the decline in IQ observed in some cases may be due to sequelae of early brain injury due to accumulation of glycosaminoglycans. Patients who were younger than 9 months at the time of transplantation had minimal injury and were still cognitively normal; thus, transplantation of stem cells to supply the missing enzyme prevented further injury.…”
Section: Discussionmentioning
confidence: 70%
“…HSCT cannot prevent or stabilize progression of the hip abnormalities in most patients [3,17,18,29]. Although data on the long-term follow-up of transplanted MPS I-H patients are very limited, the radiological characteristics, such as (sub)luxation of the hips and decreased articular cartilage, suggest that hip dysplasia may ultimately result, at least in a subgroup of patients, in pain and loss of function.…”
Section: Resultsmentioning
confidence: 99%
“…The canine model of MPS VII has a missense mutation (R166H) in the GUSB gene [8] and closely resembles the disease seen in humans [Online Mendelian Inheritance in Man (OMIM#253220)]. Current treatments for some types of MPS such as hematopoietic stem cell transplantation (HSCT) and enzyme replacement therapy (ERT) have not prevented cardiac disease [3, 9-10]. Gene therapy is being tested in animals with MPS [11].…”
Section: Introductionmentioning
confidence: 99%